Nationalist Voices in Jordan: The Street and the State by Betty S. Anderson (Austin: University of Texas Press, 2005. 288 pages.) (American Journal of Islam and Society, 2006)
Jordan has existed now for nearly 60 years, since the termination of theBritish mandate in 1946, and has generally been studied in terms of itsHashemite rulers and the “King’s men,” those who helped the Hashemitesconstruct it. These historical narratives, argues Anderson, have privilegedthe Jordanian monarchy and the “high” elements of society and, consequently,have ignored the “urban” elements that played an equal, if not agreater, role in constructing the Jordanian national identity. In this sense,Anderson gives voice to narratives that were previously unknown andunheard and, by so doing, makes a significant contribution to the body ofliterature on Jordan.She contends that the “Arab Street” “holds a key to understandingJordan in the twentieth century” and, in this regard, focuses upon the “true”Jordanian natives and their narrative. Taking a subaltern approach toJordanian history, she examines the foundation of the Jordanian NationalMovement (JNM), a coalition of leftist parties based loosely upon Arabnationalism, and its influence upon the nation’s formation. Given her uniqueapproach to Jordanian history, she admits that her work is incomplete, formany first-hand accounts and memoirs, which cannot be found, should beexamined in light of the larger body of literature on Jordan.The history of Jordan is that of post-colonial independence and nationhood,of a nation that had never existed in the hearts and minds of those whowould live within its borders until it was actually drawn on a map. In anagreement brokered in late March 1921 between Winston Chuchill, then theBritish colonial secretary, and Abdullah I, the latter would accept British ...